A new monoclinic perovskite allotype in Pr0.6Sr0.4MnO3 - Ritter, C; Radaelli, P; Lees, MR; Barratt, J; Balakrishnan, G; Paul, D (1996)
We report the observation, in Pr0.6Sr0.4MnO3, of a low-temperature phase transition between Pnma and the monoclinic space group I2/a. The I2/a allotype has never previously been observed in the (R1-xAx)MnO3 manganese perovskite system. Furthermore, this space group symmetry is not present in the recently published phase diagram obtained at 30% Mn+4, indicating that electronic doping has a direct effect on the phase stability. The structural and magnetic parameters for the new phase, as obtained from Rietveld refinements of neutron powder diffraction data, are also reported. © 1996 Academic Press.